Legal Certainty of Land Rights Based on Land Statement Letters within Industrial Plantation Forest Areas (A Study in Bengkalis Regency) - Zulfikri Toguan; Rodyahsriningsih Rodyahsriningsih; Ridho Alfahriansyah (Universitas Islam Sultan Agung, 2026)
Land occupies a strategic position in social life and national development; consequently, its control and utilization must be regulated in a manner that ensures legal certainty. In practice, particularly in rural areas, communities frequently rely on a Land Statement Letter (Surat Keterangan Tanah/ SKT) as evidence of land possession. Legal issues emerge when land possessed by communities on the basis of an SKT is located within areas designated as Industrial Plantation Forests (Hutan Tanaman Industri / HTI), where the state has granted official management permits to corporate entities. Such circumstances give rise to competing claims between communities exercising de facto control over the land and companies holding formal legal authorization issued by the government. This study seeks to examine the legal status of community land possession based on SKT within HTI areas and to assess the extent to which legal certainty is ensured, with reference to Supreme Court Decision Number 1429 K/Pdt/2022. The research adopts an empirical legal method employing a descriptive-analytical approach. Primary data were obtained through interviews with SKT holders, village officials, and representatives of the relevant company, while secondary data were collected from statutory regulations, legal scholarship, and judicial decisions. The collected data were analyzed qualitatively through a juridical approach in order to understand the practice of land control and the scope of its legal protection. The findings indicate that an SKT does not possess evidentiary value equivalent to that of a land ownership certificate, which constitutes strong legal proof of title under Indonesian land law. In cases where the disputed land is situated within HTI areas, legal certainty tends to favor parties holding formal permits issued by the state. Hence, the existence of an SKT in itself does not provide sufficient legal protection for communities unless it is followed by formal land registration in accordance with applicable land law regulations.